Comparative study of different functionalized graphene-nanoplatelet aqueous nanofluids for solar energy applications. (October 2019) - Vallejo, Javier P.; Mercatelli, Luca; Martina, Maria Raffaella; Di Rosa, Daniele; Dell'Oro, Aldo; Lugo, Luis; Sani, Elisa
Abstract: The optical properties of nanofluids are peculiar and interesting for a variety of applications. Among them, the high light extinction coefficient of nanofluids can be useful in linear parabolic concentrating solar systems, while their properties under high light irradiation intensities can be exploited for direct solar steam generation. The optical characterization of colloids, including the study of non-linear optical properties, is thus a needed step to design the use of such novel materials for solar energy exploitation. In this work, we analysed two different types of nanofluids, consisting of polycarboxylate chemically modified graphene nanoplatelets (P-GnP) and sulfonic acid-functionalized graphene nanoplatelets (S-GnP) dispersed in water, at three concentrations from 0.005 wt% to 0.05 wt%. Moderately stable nanofluids were achieved with favourable light extinction properties, as well as a non-linear optical behaviour under high input solar intensities. Highlights: Different-functionalized graphene nanoplatelets are stably suspended in water. Even extremely low nanoparticle concentrations show a high sunlight absorption. Sunlight extinction is tailored by nanoadditive concentration/functionalization. A broadband nonlinear optical response under high irradiation intensities is proved. Samples are promising for DASCs, solar vapor generation and desalination.